Conceptual framework on the continuum of change in governance structures from the perspective of member control and the life cycle of agricultural cooperatives (Management and Connections Journal, 2023)
Given the models of traditional, extended traditional, management, and corporate governance structures, this theoretical essay aims to present a conceptual framework that integrates the member control and life cycle perspectives of agricultural cooperative organizations. Starting from the continuum of changes, it is proposed that in phase 1 member control is total and is combined with the economic justification of the life cycle. In phase 2 the control is of quasi-integration and is combined with the organizational design stage of the life cycle. In phase 3 there is the separation of membership control and the life cycle goes through the stages of growth, glory, and heterogeneity. In phase 4 the control of the associates is delegated and combined with the stages of recognition and introspection. In phase 5, member control remains delegated and the life cycle reaches the stage of choice, eventually reaching the demutualization of the cooperative (phase 6).
Keywords: Governance; Conceptual framework; Cooperatives